Effect of chitosan-based coatings on the shelf life of Salmon (Salmo salar) - Souza, B. W. S. (2010)
This study aimed at determining the effect of chitosan coating on shelf life extension of salmon (Salmo salar) fillets. The success of edible coatings depends highly on their effective wetting capacity of the surfaces on which they are applied. In this context in a first stage the surface properties of salmon fillets and the wetting capacity of the coatings on fish were evaluated. In terms of wettability there were no significant differences (p > 0.05) between the solutions presenting higher values (solutions 1−4); therefore, solution 1 with a spreading coefficient (Ws) of −4.73 mN m−1, was chosen to be subsequently analyzed and applied on fish fillets. For shelf life analyses the fillets were coated and stored at 0 °C for 18 days. The control and coated fish samples were analyzed periodically for total aerobic plate count (TPC), pH, total volatile base nitrogen (TVB-N), trimethylamine (TMA), thiobarbituric acid (TBA), and ATP breakdown products (K value). The results showed that fish samples coated with chitosan presented a significant reduction (p < 0.05) for pH and K value after 6 days and for TVB, TMA, and TBA values after 9 days of storage, when compared to control samples. In terms of microbial growth, a slower increase in TPC was observed for the coated fish, indicating that chitosan-based coatings were effective in extending for an additional 3 days the shelf life of the salmon. These results demonstrate that chitosan-based coatings may be an alternative for extending the shelf life of salmon fillets during storage at 0 °C.